A cost-reduction of self-compacting concrete incorporating raw rice husk ash - Awang, Hanizam; Atan, M.N.; Zainul Abidin, Nazirah; Yusof, Nor’Aini (Taylor's University, 2016)

(untitled)
The higher material cost of self-compacting concrete (SCC) as compared to normal vibrated concrete is mainly due to its higher cement content. In order to produce economical SCC, a significant amount of cement should be replaced with cheaper material options, which are commonly found in byproduct materials such as limestone powder (LP), fly ash (FA) and raw rice husk ash (RRHA). However, the use of these byproduct materials to replace the high volumes of cement in an SCC mixture will produce deleterious effects such as strength reduction. Thus, the objective of this paper is to investigate the optimum SCC mixture proportioning capable of minimizing SCC’s material cost. A total of fifteen mixes were prepared. This study showed that raw rice husk ash exhibited positive correlations with fly ash and fine limestone powder and were able to produce high compressive and comparable to normal concrete. The SCC-mix made with quaternary cement-blend comprising OPC/LP/FA/RRHA at 55/15/15/15 weight percentage ratio is found to be capable of maximizing SCC’s material-cost reduction to almost 19% as compared with the control mix